Strategi Guru Fiqih untuk Meningkatkan Minat Belajar Siswa - Kahrani Kahrani; Ahmad Liandi Ansyar; Nurul Hikmah; Nor Hasanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the strategies implemented by Fiqh teachers to increase student learning interest and the factors influencing student interest in Fiqh learning at MTs DDI Muara Pagatan, Tanah Bubu Regency. This study used a qualitative approach with descriptive methods. The results showed that the learning strategies implemented by Fiqh teachers to increase student learning interest include the use of discussion methods, contextual approaches, interactive learning media, reward giving, and evaluation and feedback. The discussion method can create active learning and improve students' critical thinking skills. The contextual approach helps students understand Fiqh material by connecting it to everyday life. Interactive learning media such as videos, PowerPoint presentations, and quizzes make learning more engaging, while reward giving can increase student motivation and self-confidence. Furthermore, evaluation and feedback help students continuously improve their understanding. Factors influencing student interest in Islamic jurisprudence include the role of the teacher, student preparedness, the use of learning media, and the condition of facilities and infrastructure. Teachers who have a good understanding of the material and are able to implement engaging learning strategies can increase student engagement in the learning process. In conclusion, the implementation of appropriate learning strategies and the support of a positive learning environment can increase students' interest in Islamic jurisprudence. Keywords: Learning Interest, Islamic Fiqh Learning, Learning Strategies